Detection of Prune dwarf virus by one-step RT-PCR and its quantitation by real-time PCR - Jarosová, J; Kundu, J K (Journal of virological methods, 2010)
A quantitative PCR, real-time RT-PCR, and one-step real-time RT-PCR using SYBR Green-based tools for reliable detection and relative quantitation of Prune dwarf virus (PDV) in stone fruits are described. The assay reliability was tested on 55 samples from different hosts and regions. The sensitivity of the assay was also compared with other assays with different primers. Two plant-expressed genes, actin and 18S rRNA, were used as housekeeping genes for accurate quantitation of PDV in stone fruit trees. The expression of the gene for actin and the 18S ribosomal RNA gene corresponded with each other accurately, with standard deviation values of 1.905 cycles on average, 1.36 for Prunus persica, and 2.45 for other Prunus species tested. The results of this study support the need to use more than one housekeeping gene as an internal control to avoid possible errors caused by unstable internal control gene mRNA expression when quantifying the extent of PDV infection.
Keywords: RNA virová; Prunus; RNA, Plant; RNA ribozomální 18S; Ilarvirus; referenční standardy; Diamines; aktiny; Benzothiazoles; Viral Load; polymerázová řetězová reakce s reverzní transkripcí; Quinolines; Reverse Transcriptase Polymerase Chain Reaction; barvení a značení; Reference Standards; virová nálož; benzothiazoly; RNA rostlin; fluorescenční barviva; Fluorescent Dyes; rostlinné proteiny; organické látky; Organic Chemicals; Plant Proteins; slivoň; RNA, Viral; diaminy; Actins; RNA, Ribosomal, 18S; Staining and Labeling; chinoliny